The dental enamel proteome of Paranthropus robustus - (:unkn) unknown (My University, 2023)
It has been consistently observed that protein fragments survive beyond the diagenetic limits of DNA, allowing for the recovery of biomolecular information deeper in time, even from temperate and subtropical climates. Phylogenetically informative dental enamel proteins have been recovered from Gigantopithecus blacki (~1.9 Ma) and Homo antecessor (~8-900 ka), clarifying the taxonomic position of these two species. Here, we report the recovery of dental enamel proteins from four Paranthropus robustus (P. robustus) specimens from Swartkrans, South Africa, dated to 2.2-1.8 Ma (SK830, SK835, SK850, SK14132). We employed a digestion-free extraction protocol and tandem mass spectrometry for peptide sequencing. To reconstruct protein sequences from MS/MS spectra a combination of different data search strategies was employed. Specimens SK835 and SK850 were identified as biological males, through the confident identification of amelogenin Y (AMELY)-specific peptides. This opens the possibility of reassessing our understanding of sexual dimorphism in P. robustus and potentially in other early hominins. The reconstructed enamel protein sequences from P. robustus were compared to their orthologous ones from all extant and some extinct hominid taxa. The multi sequence alignment enabled us to clarify the variation that exists within the hominid group. Although the coverage breath of the ancient enamel proteome sequence recovered is admittedly limited, we identified potentially informative single amino acid polymorphisms, which enabled the tentative phylogenetic placement of P. robustus. Extending this work to other African hominin species will provide a better understanding of the variation within and between these taxa in Africa.
Keywords: African Research